Growth Response of Dipterocarpus tuberculatus and Shorea roxburghii Seedlings to Astraeus odoratus: DOI: 10.32526/ennrj.17.3.2019.25 - Kaewgrajang, Tharnrat; Sakolrak, Baramee; Sangwanit, Uthaiwan (Environment and Natural Resources Journal, 2019)
In this study, we investigated the effects of the highly prized ectomycorrhizal (ECM) mushroom, Astraeus odoratus, on the growth of Dipterocarpus tuberculatus Roxb. and Shorea roxburghii G. Don seedlings. The two seedling species were inoculated using two methods: 1) spore suspension of 25 mL/seedling; and 2) hyphal suspension of 25 mL/seedling. On harvesting, it was found that 30-60% of the roots formed by the inoculated seedlings were ectomycorrhizal roots. Seedling development was influenced by the inoculation method and the host plant species. A higher growth response was observed in the S. roxburghii seedlings inoculated with A. odoratus compared to D. tuberculatus seedlings. Moreover, the non-inoculated S. roxburghii seedlings had a lower growth response than D. tuberculatus seedlings, but their growth response was significantly higher than D. tuberculatus seedlings inoculated with a spore or hyphal suspension of A. odoratus. However, there was no difference between the effects of the spore and hyphal suspension treatments. Therefore, both the inoculation methods can be used to enhance the growth of seedlings, especially that of S. roxburghii.